Protein Kinase CK1α Sustains B-Cell Receptor Signaling in Mantle Cell Lymphoma - Manni, Sabrina; Fregnani, Anna; Quotti Tubi, Laura; Spinello, Zaira; Carraro, Marco; Scapinello, Greta; Visentin, Andrea; Barilà, Gregorio; Pizzi, Marco; Dei Tos, Angelo Paolo; Vianello, Fabrizio; Zambello, Renato; et al. (Frontiers in Oncology, 2021)
Mantle Cell Lymphoma (MCL) is still an incurable B-cell malignancy characterized by poor prognosis and frequent relapses. B Cell Receptor (BCR) signaling inhibitors, in particular of the kinases BTK and PI3K/, have demonstrated clinically meaningful anti-proliferative effects in B cell tumors. However, refractoriness to these drugs may develop, portending a dismal prognosis. Protein kinase CK1α is an emerging pro-growth enzyme in B cell malignancies. In multiple myeloma, this kinase sustains β-catenin and AKT-dependent survival and is involved in the activation of NF-B in B cells. In this study, we analyzed the role of CK1α on MCL cell survival and proliferation, on the regulation of BCR-related BTK, NF-B, PI3K/AKT signaling cascades and the effects of CK1 chemical inhibition or gene silencing in association with the BTK inhibitor Ibrutinib or the PI3K/ inhibitor Duvelisib. CK1α was found highly expressed in MCL cells as compared to normal B cells. The inactivation/loss of CK1α caused MCL cell apoptosis and proliferation arrest. CK1α sustained BCR signaling, in particular the NF-B, AKT and BTK pathways by modulating the phosphorylation of Ser 652 on CARD11, Ser 536 p65 on NF-B, Ser 473 on AKT, Tyr 223 on BTK, as well as the protein levels. We also provided evidence that CK1α-mediated regulation of CARD11 and BTK likely implicates a physical interaction. The combination of CK1α inhibition with Ibrutinib or Duvelisib synergistically increased cytotoxicity, leading to a further decrease of the activation of BCR signaling pathways. Therefore, CK1α sustains MCL growth through the regulation of BCR-linked survival signaling cascades and protects from Ibrutinib/Duvelisib-induced apoptosis. Thus, CK1α could be considered as a rational molecular target for the treatment of MCL, in association with novel agents.